PHENOMENOLOGY AND ITS AESTHETIC POTENTIAL - Скальська, Д. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the analysis of anthropologically oriented aesthetic concepts that are most substantially and originally viewed in phenomenological existential philosophical tradition. F. Brentano, E. Husserl, M. Merleau-Ponty, R. Ingarden, M. Dufrenne present the range of philosophical anthropological researches where the specific method and categorical variety of phenomenological aesthetics are elaborated.